Comparative virulence of blood and stool isolates of Shigella sonnei. - Seymour, C (1994)
Shigellemia is rare in developed countries and might result from the emergence of unusually virulent strains. We compared systemic invasiveness markers of isolates from the blood of 3 temporally clustered patients with Shigella sonnei bacteremia in Boston with those of 11 unrelated contemporaneous strains from stools of people in New England. We found no difference between the two groups in O-chain length by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, mouse 50% lethal dose, in vivo response to iron, and susceptibility to serum, which varied from moderately susceptible to ultrasusceptible. Mean intraperitoneal 50% lethal doses of smooth form I colonies for mice were equally low (10(5.8) CFU) in both groups, and the 50% lethal doses were lowered equally further in the two groups by predosing with iron to levels useful in mouse model sepsis studies. S. sonnei bacteremia may reflect compromised host defenses, not bacterial virulence.